2016
DOI: 10.1152/ajpheart.00732.2015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of passive stretch on muscle blood flow, oxygenation and central cardiovascular responses in healthy young males

Abstract: The aim of this study was to examine the effect of skeletal muscle stretching on peripheral, central, and autonomic cardiovascular responses in humans. Twelve healthy males completed a controlled passive stretch of the plantar flexors for 4 min at three different intensities. Doppler ultrasound velocimetry and imaging techniques assessed mean leg blood flow (MLBF), antegrade blood flow, and retrograde blood flow of the popliteal artery. Near-infrared spectroscopy assessed the concentration of deoxygenated hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 53 publications
4
66
0
Order By: Relevance
“…Acute passive stretching. The participants rested in a supine position during stretching for the knee extensor (Venturelli et al 2019) and in a prone position for plantar flexor muscles (Kruse et al 2016) for 20 min before starting the data collection and remained in this position throughout the entire duration of the data collection. The two stretching bouts were separate by 60 min rest, during which the participant remained at rest on a medical bed.…”
Section: Maximum Isometric Voluntary Contraction (Mvc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Acute passive stretching. The participants rested in a supine position during stretching for the knee extensor (Venturelli et al 2019) and in a prone position for plantar flexor muscles (Kruse et al 2016) for 20 min before starting the data collection and remained in this position throughout the entire duration of the data collection. The two stretching bouts were separate by 60 min rest, during which the participant remained at rest on a medical bed.…”
Section: Maximum Isometric Voluntary Contraction (Mvc)mentioning
confidence: 99%
“…The improvement may stem from repeated changes inẎ during PS and from its effect on NO bioavailability. PS training repeatedly exposed the vessels to increased levels ofẎ (Kruse et al 2016;Venturelli et al 2017aVenturelli et al , 2019, thus stimulating endothelial mechanotransduction signalling in smooth muscle cells that results in vasodilatation ( , Green et al 2017a. Such repeated alterations inẎ over time can be considered as a kind vascular preconditioning that may lead to increase NO bioavailability (Green et al 2017a;Bisconti et al 2019).…”
Section: Ps Training-induced Changes In Vascular Functionmentioning
confidence: 99%
“…However, no work evaluating the effect of SS duration in adolescents exists in the literature. Studies related to muscle blood flow used conventional Doppler, micro-CT analysis, gamma scintillation counter or experimental model methods [12,23]. These studies have concluded that there is a reduction in local blood flow during stretching, with an acute post-stretch hyperemic response after stretching and a vascularity increase in the chronic period.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Mayhew et al [23] found that a 1-minute rest interval between sets resulted in higher total leukocytes as compared with that of 3 minutes. Kruse et al [24] demonstrated that in humans retrograde muscle blood flow decreased following stretching. Otsuki et al [25] observed a decrease in blood volume accompanied by a general decline in microvascular muscle oxygenation induced by stretching.…”
Section: Discussionmentioning
confidence: 99%